The Influence of Customer Relationship Management Strategy on PT Pupuk Indonesia's Customer Satisfaction - Muhamad Tony Houston (Green Publisher Indonesia, 2025)
Customer Relationship Management (CRM) has become a critical strategic approach for companies to maintain competitive advantage and build long-term relationships with customers. This research aims to examine and analyze the influence of Customer Relationship Management (CRM) on customer satisfaction at PT Pupuk Indonesia. The research object is the consumers of PT Pupuk Indonesia, with the population consisting of all company customers and a sample of 96 respondents selected using purposive sampling method. The analytical method used is simple regression analysis with SPSS software. The results indicate that CRM has a significant positive influence on customer satisfaction with a correlation coefficient of 0.671 and coefficient of determination (R²) of 0.445, meaning CRM explains 44.5% of the variation in customer satisfaction. The t-test results show t-value of 8.780 > t-table of 1.984 with significance level of 0.000 < 0.05, confirming that CRM significantly affects customer satisfaction. This demonstrates that effective customer relationship management, such as systematic customer data storage, efficient service, and responsive communication, can enhance customers' positive perceptions of the company. Based on these findings, it is recommended that PT Pupuk Indonesia continue to strengthen its CRM implementation, improve service quality, and expand the use of digital technology in customer interactions to better meet customer needs and enhance the company's competitiveness in the long term.